Naratif mualaf dan aktivis dakwah terhadap dasar penamaan saudara baru - Mohd Al Adib Samuri,; Azlan Shah Nabees Khan,; Razaleigh Muhamat @ Kawangit, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Although the legal provision with regard to mualaf (new Muslim convert) registration is clearly stated in the state Islamic enactments, there is no any written law to determine the naming for mualaf. Starting from the year 1981, Malaysian religious authority published an official guideline on the naming for individuals who convert to Islam which is lately being criticised by some mualafs. This article intends to discuss the concept of naming from the Islamic perspective, issues related to naming of new Muslims and naming policy that administered at the religious institutions. Besides of that, the article also will discuss the narratives of mualaf regarding the implication of Muslim naming policy towards their personal life, identity, and family dynamic. Therefore, this research has conducted an in-depth semi structured interview with 11 mualaf and Muslim preachers who experience facing and handling issues related to identity change after conversion. The research found that although there is no any written law concerning the naming method for mualaf, however, the guideline on the naming published by the Department of Islamic Advancement of Malaysia (Jakim) has been taken as a policy in determining the naming for mualaf. Despite some mualaf agree to the practice of changing their previous names to Arab-Islam style names, however, there are several implications caused by the change since their identity record is not synchronized between all government and private agencies. The research also found that the practice of changing the name to Arab-Islam style name for mualaf has affected their ethnic identity and caused them problems with their family. This research is important to re-evaluate the current naming policy for mualaf to make it more flexible and understand the mualaf’s initial social culture in order to ensure the continuity of da’wah in Malaysia.